2019
DOI: 10.1155/2019/8690650
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Mechanical Properties and Heat Resistance of PLLA-b-PEG-b-PLLA by Melt Blending with PDLA-b-PEG-b-PDLA for Potential Use as High-Performance Bioplastics

Abstract: Ecofriendly poly(L-lactide)-b-poly(ethylene glycol)-b-poly(L-lactide) (PLLA-b-PEG-b-PLLA) are flexible bioplastics. In this work, the blending of poly(D-lactide)-b-poly(ethylene glycol)-b-poly(D-lactide) (PDLA-b-PEG-b-PDLA) with various blend ratios for stereocomplex formation has been proved to be an effective method for improving the mechanical properties and heat resistance of PLLA-b-PEG-b-PLLA films. The PLLA-b-PEG-b-PLLA/PDLA-b-PEG-b-PLDA blend films were prepared by melt blending followed with compressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…It should be suggested that the sc-Xc,DSC increased with the PDLA-PEG-PDLA ratio. The higher PDLA-PEG-PDLA ratio gave a more substantial PDLA fraction for stereocomplex formation with PLLA end blocks of PLLA-PEG-PLLA [11]. The result shows that all the blended films with tetracycline were higher the percentage of homo and stereocomplex crystalline than the film without tetracycline.…”
Section: Thermal Transition Propertiesmentioning
confidence: 89%
See 1 more Smart Citation
“…It should be suggested that the sc-Xc,DSC increased with the PDLA-PEG-PDLA ratio. The higher PDLA-PEG-PDLA ratio gave a more substantial PDLA fraction for stereocomplex formation with PLLA end blocks of PLLA-PEG-PLLA [11]. The result shows that all the blended films with tetracycline were higher the percentage of homo and stereocomplex crystalline than the film without tetracycline.…”
Section: Thermal Transition Propertiesmentioning
confidence: 89%
“…The 93 and 142 J/ g are theoretical 100%Xc for homocrystallites and stereocomplex crystallites, respectively. WPLA is a weight fraction of PLA that is 0.83 [11].…”
Section: Characterizationmentioning
confidence: 99%
“…Poly(L-lactide)-b-polyethylene glycol-b-poly(L-lactide) triblock copolymers (PLLA-PEG-PLLA) showed greater flexibility and faster crystallization-rate than PLLA due to flexibility of PEG middleblocks causing an enhanced plasticizing effect [10,11]. However, the heat resistance of PLLA-PEG-PLLA was still poor [12]. The heat resistance of PLLA and PLLA-PEG-PLLA is directly related to degree of crystallinity [13−15].…”
Section: Introductionmentioning
confidence: 99%